Sectoral Value Added : Electricity Elasticities across Countries - Hovhannisyan, Shoghik; Stamm, Kersten (World Bank, Washington, DC, 2021)
Many developing countries face severe electricity constraints, which are reflected in low electrification rates, frequent and prolonged outages, and high electricity tariffs, all of which result in low electricity consumption that impedes economic development. This study estimates the impact of electricity consumption on value added through reduced form equations for three sectors: agriculture, manufacturing, and services. It uses panel data on 126 countries for 1996–2014 from the International Energy Agency and World Development Indicators databases. To control for endogeneity and reverse causality bias in the ordinary least squares estimators, the study applies two-step difference and system panel generalized method of moments estimation techniques, which improve the ordinary least squares estimates by applying lags of the explanatory variables as instruments that are not correlated with the error term and account for countries’ fixed effects generating bias in the coefficients. The estimation results indicate that electricity consumption has a significant and positive impact on the manufacturing sector’s value added in non-highincome countries (with an elasticity of 0.022). By contrast, the electricity consumption elasticities are insignificant in agriculture and services in non-high-income countries, as the production technologies of these industries vary substantially across income groups compared with those in manufacturing. Finally, using all the countries in the sample produce positive and significant results for all sectors, with the highest elasticity of 0.036 in manufacturing.